(untitled) (Bangladesh Journal of Medicine, 2024)
An uncommon inflammatory disorder that affects the orbit of the eye is called orbital pseudotumor. It can present in a variety of clinical ways. Its precise etiology is yet unclear, although an immunemediated response is thought to be involved. A 35-year-old woman arrived to the neurology clinic with symptoms of double vision and persistent headache. There was a mild protrusion of the left eye from the orbital cavity, the eyeball medially rotated in the primary position, and restriction of leftsided eyeball movement towards the left side with complaints of increasing double vision during the attempt. She had no recent medical history or traumatic experiences. Over the course of three weeks, the initial discomfort had increased. There were no known allergies, however the patient was normotensive. Upon examination, the left eye had flare, slight anterior chamber cell, erythema, and eyelid edema. Magnetic resonance imaging showed involvement of the optic nerve, thickening of the extraocular muscles, and augmentation of orbital soft tissues. Inflammatory markers were high in the laboratory results. An orbital pseudotumor was diagnosed. The patient was treated with Inj Methylprednisolone followed by corticosteroids, her symptoms improved and the inflammatory condition subsided. A thorough approach including imaging scans, laboratory testing, and clinical evaluation is necessary for its diagnosis. The importance of recognizing an uncommon presentation and management of orbital pseudotumor with was highlighted in this case report. Bangladesh J Medicine 2025; 36: 71-74